Pergeseran Makna Dalam Penerjemahan Syair Populer di Gowa - Tedi Dwi Firmansyah; Tarman Tarman; Muh. Ali Imran (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the shift in meaning in the translation of popular poetry in Gowa. The data sources used in this research are books, or various sources or references on the internet, by comparing the original text and translations in Indonesian. The research results found that regarding shifts in meaning in the translation of popular poetry in Gowa, 26 pieces of data were found that experienced shifts in meaning. A total of 15 data experienced a shift from specific to generic meaning, and 11 data experienced a shift from generic to specific meaning. Shifts from specific to generic meaning or vice versa are often found in interjection translations. Interjections in Indonesian and Makassar languages ​​both vary, but the use of interjections in both languages ​​must still pay attention to the context of the utterance.